Peran Kepemimpinan dalam Pengembangan Sistem Pemerintahan Berbasis Elektronik (SPBE) di Kota Medan - Purba, Widya Helen Anjalina; Sinaga, Eko Pranata; Ivanna, Julia (Majalah Ilmiah METHODA, 2024)
This research explores the role of leadership in the development of Electronic Government Systems (EGS) in Medan City. Using a qualitative approach with a literature review research design, the study analyzes how leadership influences the implementation of information technology in government administration. Findings indicate that strong and technology-oriented leadership can inspire innovation and transformation in EGS, facilitate community involvement, and enhance public service efficiency. Managerial and policy implications are outlined to support the sustainable development of EGS in Medan City.